Effectiveness of Taping for the Short-Term Treatment of Pain and Walking Speed in Patients with Plantar Fasciitis - Mira Muhammad; Angela BM Tulaar; Rosiana Pradanasari; Saptawati Bardosono (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Plantar fasciitis causes pain in the heel and medial arch of the foot can interfere daily activities. Taping theplantar fasciitis will reduce pain by reducing strain on the plantar fascia during standing and ambulation.Objective: to see the effect of taping on pain and walking speed.Methods: fifteen subjects received taping and ultrasound diathermy therapy for one week. Fifteen othersubjects received ultrasound therapy alone. Pain measured by Visual Analogue Scale (VAS) and the walkingspeed is measured in meters / sec.Results: VAS score started to differ significantly on the first day after treatment (p = 0.008) and continuesuntil the last day of evaluation. On the first day, the VAS score changes differs significantly (p = 0.002). Butin the evaluation of the days, the change of VAS scores were not significantly different. VAS score changes onthe seventh day compared to the initial evaluation found significant (p <0.001). With multivariate analysis ofrepeated measurements, VAS scores in each group decreased significantly (p <0.001), but the decrease in VASscore taping group were significantly better compared with non-taping group (p = 0.004).Conclusion: combination of taping and ultrasound diathermy for people with plantar fasciitis can be used asa modality to reduce pain more quickly.Keywords:plantar fasciitis, taping, ultrasound diathermy, visual analog scale, walking speed.